Growth performance, visceral and blood parameters, and egg production and quality of Japanese quails (Coturnix japonica) supplemented with black soldier fly (Hermetia illucens) larvae oil - Dunting, Ma. Jessa A.; Evacitas, Florence C. (Cebu City, Cebu Department of Biology and Environmental Science, College of Science, University of the Philippines Cebu, 2022)
Black soldier fly larvae (BSFL) can be processed to extract the fat and produce a defatted protein rich meal. The use of BSFL as an alternative protein source has been the focus of majority of the published research on BSFL in animal diet. However, there is limited literature reporting on the use of its fat content in animal nutrition. The present study evaluated the effects of BSFL oil as a fat source or as an effective feed supplement on the productive performance of Japanese quails as assessed by the following parameters: growth performance, visceral and blood parameters, and egg production and quality. A total of 36 eighteen-day-old female quails were randomly assigned to three treatment groups and a control group. The three treatment groups were fed with a basal diet supplemented with 3 % BSFL oil, 3 % coconut oil, or 10 % dried BSFL. The control group was fed with a basal diet with no supplementation. Results showed that the quails fed with different dietary treatments (3 % BSFL oil, 3 % coconut oil, and 10% dried BSFL) did not significantly differ in their growth performance, visceral and blood parameters, and egg quality when compared to those in the control group. However, results showed that the egg production rate was significantly highest, with an improved FECR value, for quails fed with a diet supplemented with 3 % BSFL oil (18.6 %) and significantly lowest (P = 0.027) in quails fed with only the basal diet (8.71 %). These results indicate that supplementing 3 % BSFL oil to the diets of the quails could improve egg production rate without showing an adverse effect on growth performance, visceral and blood parameters, and egg quality. This further suggests that BSFL oil can be used as a dietary fat supplement for Japanese quails.
Thesis (Bachelor of Science in Biology). University of the Philippines Cebu. July 2022.